Physiotherapy and Occupational Therapy in Acute Neurology - Seitz, Rüdiger J.; Kolman, Aschwin; Kraft-Kornwinkel, Birgit; Robbers, Sabine (Neurology International Open, 2018)
Therapy of neurological patients comprises, beyond medical treatment, the treatment of functional deficits which result from a neurological disease such as stroke. Physiotherapy aims at enabling bedridden neurological patients to become mobile again using training of movement and coordination. In cooperation with occupational therapists, patients are trained to become able to perform activities of daily living again. In addition, multimodal activating/assisting exercises are mandatory to counteract the deficit-related development of joint contractures. The rationale for these exercises are neurophysiological findings about postlesional cerebral plasticity. Moreover, parametric scales have been developed to assess neurological disturbances and to monitor their resolution in an observer-independent fashion. This allows communication across institutions and to assess the efficacy of physiotherapy and occupational therapy.
Keywords: physiotherapy; occupational therapy; scales; therapeutic goals; stroke unit